A Sequence-Ready BAC Contig of the GABAA Receptor Gene Cluster Gabrg1–Gabra2–Gabrb1 on Mouse Chromosome 5 - Lengeling, Andreas; Wiltshire, Tim; Otmani, Chris; Bućan, Maja (Genome Research, 1999)
The type-A receptors for the neurotransmitter GABA (γ-aminobutyric acid) are ligand-gated chloride channels that mediate postsynaptic inhibition. The functional diversity of these receptors comes from the use of a large repertoire of subunits encoded by separate genes, as well as from differences in subunit composition of individual receptors. In mammals, a majority of GABAAreceptor subunit genes are located in gene clusters that may be important for their regulated expression and function. We have established a high-resolution physical map of the cluster of genes encoding GABAA receptor subunits α2 (Gabra2), β1 (Gabrb1), and γ1 (Gabrg1) on mouse chromosome 5. Rat cDNA probes and specific sequence probes for all three GABAA receptor subunit genes have been used to initiate the construction of a sequence-ready contig of bacterial artificial chromosomes (BACs) encompassing this cluster. In the process of contig construction clones from 129/Sv and C57BL/6J BAC libraries were isolated. The assembled 1.3-Mb contig, consisting of 45 BACs, gives five- to sixfold coverage over the gene cluster and provides an average resolution of one marker every 32 kb. A number of BAC insert ends were sequenced, generating 30 new sequence tag sites (STS) in addition to 6 Gabr gene-based and 3 expressed sequence tag (EST)-based markers. STSs from, and surrounding, theGabrg1–Gabra2–Gabrb1 gene cluster were mapped in the T31 mouse radiation hybrid panel. The integration of the BAC contig with a map of loci ordered by radiation hybrid mapping suggested the most likely genomic orientation of this cluster on mouse chromosome 5: cen–D5Mit151–Gabrg1–Gabra2–Gabrb1–D5Mit58–tel. This established contig will serve as a template for genomic sequencing and for functional analysis of the GABAA gene cluster on mouse chromosome 5 and the corresponding region on human chromosome 4.The sequence data described in this paper have been submitted to the GenBank/GSS data libraries under accession nos.AF156490 and AQ589406–AQ589436.